2018
DOI: 10.1029/2017jc013622
|View full text |Cite
|
Sign up to set email alerts
|

Floe Size Effect on Wave‐Ice Interactions: Possible Effects, Implementation in Wave Model, and Evaluation

Abstract: Wind waves may play an important role in the evolution of sea ice. That role is largely determined by how fast the ice layer dissipates the wave energy. The transition from a continuous layer of ice to a series of broken floes is expected to have a strong impact on the several attenuation processes. Here we explore the possible effects of basal friction, scattering, and dissipation within the ice layer. The ice is treated as a single layer that can be fractured in many floes. Dissipation associated with ice fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(133 citation statements)
references
References 62 publications
6
127
0
Order By: Relevance
“…Stopa et al (2018) have also determined attenuation further into the ice pack during Wave Experiment 3, using a larger domain thanks to wave heights derived from Sentinel 1 SAR imagery. The associated processes appear very different from what is found in pancake ice and is described by Boutin et al (2018) and discussed by Ardhuin et al (2018). Montiel et al (2018) further analyze wave attenuation and directional spreading during the large wave event of Wave Experiment 3.…”
Section: Wavesmentioning
confidence: 86%
“…Stopa et al (2018) have also determined attenuation further into the ice pack during Wave Experiment 3, using a larger domain thanks to wave heights derived from Sentinel 1 SAR imagery. The associated processes appear very different from what is found in pancake ice and is described by Boutin et al (2018) and discussed by Ardhuin et al (2018). Montiel et al (2018) further analyze wave attenuation and directional spreading during the large wave event of Wave Experiment 3.…”
Section: Wavesmentioning
confidence: 86%
“…A recent study has found that the basal melt rate may also be influenced by floe size (Horvat and Tziperman, 2018). Floe size can also impact the propagation of waves under the ice (Boutin et al, 2018;Meylan and Squire, 1994;Squire, 2007). The assumption of a fixed floe size also precludes sea ice models from accurately representing the role of processes within sea ice evolution that can change floe size such as lateral melting and wave induced fragmentation of floes.…”
Section: Introductionmentioning
confidence: 99%
“…Sea ice in the region typically referred to as the marginal ice zone (MIZ)—by definition influenced by the action of waves—may have different concentration, thickness, and mechanical properties and may consist of different ice types, from compact, semicontinuous ice sheet, through large, thick ice floes (bare or covered with snow) and crushed ice pieces, pancake ice, to a dense mixture of frazil crystals and water. In recent years, the transformation of waves as they propagate through sea ice—different types of sea ice—has become subject of extensive observational and theoretical research (Ardhuin et al, ; Bennetts & Squire, ; Boutin et al, ; Kohout & Meylan, ; Kohout, Meylan, & Plew, ; Meylan, Bennetts, & Kohout, ; Squire, ; Sutherland, Christensen, & Rabault, , and references therein). The observed attenuation rates in sea ice (see, e.g., the recent study by Stopa et al, ) vary over a few orders of magnitude, from less than 10 −6 m −1 to over 10 −3 m −1 , suggesting that different combinations of processes are responsible for the decay of wave energy in different ice and wave conditions.…”
Section: Introductionmentioning
confidence: 99%